Державний контроль якості інвестицій як інструмент інвестиційного регулювання. - Злакоман, І.М.; Злакоман, И.М.; Zlakoman, I. (My University, 2011)
The article is devoted to state control in the ﬁ eld of realization of the foreign investment in Ukraine. In particular, the attention has been turned on next questions: about inalienability of state control for realization of investment projects from the general process of assistance to bringing in of the foreign investing and determination of its basic principles. Also, was made the analy- sis of development of Ukrainian legislation about foreign investments, was formulated the recommendation on the improvement of the system of state control for realization of investment projects in Ukraine.
Злакоман, І.М. Державний контроль якості інвестицій як інструмент інвестиційного регулювання. / І.М. Злакоман // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. – Одеса : Фенікс, 2011. – Вип. 43. С. 202- 210.
Keywords: Державний контроль якості; Інвестиційне регулювання; Інвестиції; Іноземне інвестування в Україні; Иностранное инвестирование в Украине; Инвестиции; Инвестиционное регулирование; Государственный контроль качества; State quality control; investment regulation; investment; Foreign investment in Ukraine